CHANGED, EVERYTHING CHANGED IN MY LIFE: ELDERLY EXPERIENCES IN COEXISTENCE GROUPS AT IJUÍ/RS COMMUNITY. - Joseila Sonego; Viviane Tolfo Cappellari; Marinês Tambara Leite (Universidade Federal de Goias, 2002)
This work had the objectivity to know the reasons that make elderly regular visitors of groups andtheir life changes. A study with qualitative, explorative and descriptive nature. A piece of information occurred by aparticipating observant and a structural interview made with mixed recording questions: what were the reasons thatmade you participate with this group? Did you make any change in your life since you ve started to frequent it?About eight elderly were interviewed in these coexistence groups here in Ijuí/RS. Analysis, classified thoseinformations in two categories. The reasons pointed were personal interaction, the act of share joy, love, sadnessand knowledge. Needless to say, rescue vanity, pleasure, satisfaction, and joy of being with other people. Thegroup is considered a social space; in witch they realize activities like the act of speaking, laughing, dancing andstrengthening. When participating in these groups, they have physical and mental changes. They even have afamiliar support and encourage continuing at these groups.